HCV core protein interaction with gC1q receptor inhibits Th1 differentiation of CD4+ T cells via suppression of dendritic cell IL-12 production - Stephen N. Waggoner; Caroline Hall; Young S. Hahn (2007)
Abstract Dendritic cells (DCs) isolated from patients with chronic hepatitis C virus (HCV) infection display an impaired capacity to generate type 1 CD4+ T cell immunity. Several reports have described an immunomodulatory function for the HCV core protein, and circulating core has been shown to associate with the putative gC1q receptor, gC1qR, expressed on host immune cells. However, the molecular mechanism(s) of HCV core-mediated DC dysfunction has not been defined. Herein, ligation of gC1qR on human monocyte-derived DCs (MDDCs) with HCV core or anti-gC1qR agonist antibody was shown to inhibit TLR-induced IL-12 production but not the production of other TLR-stimulated cytokines. Furthermore, engagement of gC1qR on MDDCs resulted in reduced IFN-γ secretion by allogeneic CD4+ T lymphocytes during mixed lymphocyte culture. Differentiation of CD4+ T cells cocultured with HCV core- or anti-gC1qR antibody-treated MDDCs was also skewed toward production of Th2 cytokines, including IL-4. Importantly, that addition of IL-12 rescued IFN-γ production and Th1 differentiation by CD4+ T cells. Therefore, engagement of gC1qR on DCs by HCV core limits the induction of Th1 responses and may contribute to viral persistence.